Surface-Induced Formation and Redox-Dependent Staining of Outer Membrane Extensions in Shewanella oneidensis MR-1 - Chong, Grace W.; Pirbadian, Sahand; El-Naggar, Mohamed Y. (Frontiers in Energy Research, 2019)
The metal-reducing bacterium Shewanella oneidensis MR-1 produces extensions of its outer membrane (OM) and periplasm that contain cytochromes responsible for extracellular electron transfer (EET) to external redox-active surfaces, including minerals and electrodes. While the role of multi-heme cytochromes in transporting electrons across the cell wall is well established, their distribution along S. oneidensis OM extensions is also thought to allow lateral electron transport along these filaments. These proposed bacterial nanowires, which can be several times the cell length, would thereby extend EET to more distant electron acceptors. However, it is still unclear why these extensions form, and to what extent they contribute to respiration in living cells. Here, we investigate physical contributors to their formation using in vivo fluorescence microscopy. While previous studies focused on the display of S. oneidensis outer membrane extensions (OMEs) as a response to oxygen limitation, we find that cell-to-surface contact is sufficient to trigger the production of OMEs, including some that reach >100 μm in length, irrespective of medium composition, agitation, or aeration. To visualize the extent of heme redox centers along OMEs, and help distinguish these structures from other extracellular filaments, we also performed histochemical redox-dependent staining with transmission electron microscopy on wild type and cytochrome-deficient strains. We demonstrate that redox-active components are limited to OMEs and not present on other extracellular appendages, such as pili and flagella. We also observed that the loss of 8 functional periplasmic and outer membrane cytochromes significantly decreased both the frequency and intensity of redox-dependent staining found widespread on OMEs. These results will improve our understanding of the environmental conditions that influence the formation of S. oneidensis OMEs, as well as the distribution and functionality of EET components along extracellular appendages.